PENGGUNAAN MEDIA KARTU BERGAMBAR UNTUK PENGEMBANGAN KEMAMPUAN BAHASA PADA ANAK USIA 4-5 TAHUN - Ramadhani, Septiyanti; Halida, Halida; Lukmanulhakim, Lukmanulhakim (Universitas Tanjungpura, 2024)
This research aims to describe the use of picture card media to develop language skills in children aged 4-5 years. The research method used is descriptive with a qualitative approach. The subjects in this research were two group A class teachers. The data collection techniques used in this research were observation, interviews and documentation. The data analysis used is data collection, data reduction, data presentation and drawing conclusions. The data validity checking technique uses triangulation. The results of this research show that: (1) Learning planning for the use of picture card media for language skills in children aged 4-5 years is in accordance with the RPPH made by the teacher which refers to the curriculum made by the institution. (2) The implementation of the use of picture card media for language skills in children aged 4-5 years is carried out in stages starting from the teacher introducing and teaching one by one the vocabulary and letter sound symbols, the teacher preparing tools and materials,the teacher dividing them into several groups, and the teacher provides activities to the children. (3) Evaluation of learning using picture card media for language skills in children aged 4-5 years is carried out by the teacher during the learning process and the teacher assesses the results of the child's activities and then gives grades according to the child's development criteria, namely: BB (Not yet Developed), MB (Starting Developing), BSH (Developing According to Expectations), and BSB (Developing Very Well) on the daily assessment format sheet in the RPPH.